1983
DOI: 10.1042/bj2150213
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte glutathione S-transferase. Electrophoretic identification of two enzyme forms

Abstract: Starch-gel electrophoresis was used to demonstrate two forms of glutathione S-transferase in human erythrocytes. Whereas considerable inter-individual differences in enzyme activity and electrophoretic patterns were detected, intra-individual differences were small.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1984
1984
1995
1995

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 8 publications
(12 reference statements)
1
0
0
Order By: Relevance
“…Normal erythrocyte GST activities towards CDNB vary considerably between individuals (6-10 fold) [125,141] (also confirmed in this thesis), and it was suggested early that the cause might be undetected (genetic) variation [142]. Fazi and coworkers showed that GSTp actually exists in two forms [50] that can be separated using ion-exchange chromatography.…”
Section: Glutathione S-transferasesupporting
confidence: 62%
“…Normal erythrocyte GST activities towards CDNB vary considerably between individuals (6-10 fold) [125,141] (also confirmed in this thesis), and it was suggested early that the cause might be undetected (genetic) variation [142]. Fazi and coworkers showed that GSTp actually exists in two forms [50] that can be separated using ion-exchange chromatography.…”
Section: Glutathione S-transferasesupporting
confidence: 62%